Building Capacity to Make Transport Work for Women and Men in Vietnam : Gender and Transport Challenges - World Bank (Washington, DC, 2012)
Women and men use rural and urban transport for different purposes based on their socially determined roles and responsibilities. Poor rural transport systems limit access to markets, education, and health services for all, but even more so for women and girls. Female mobility is often constrained by heavy domestic work-loads and time spent traveling by foot, carrying heavy loads over rough trails. Time poverty combines with cultural restrictions to limit women's and girls' economic, educational opportunities and participation in community decision-making, particularly for ethnic minority women in remote mountainous areas. Gender differences in mobility and access are also affected by ability to pay for transport services. Most women have more limited access to financial and other resources, and inadequate voice in local level transport priority setting than men. Gender and Transport capacity building needs to be grounded in practical, on-the ground country realities in the transport sector and draw on the experience of transport specialists who have addressed gender in their work or clearly understand the entry points. Participatory gender and transport capacity building that provides opportunities for applying what is learned to transport problems is more effective than a lecture format.